PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PELAJARAN PERAWATAN MESIN KENDARAAN RINGAN - Moh. Fahri Yasin; Teguh Teguh (Akademika, 2021)
Abstract:. The purpose of this study is to test 1) The existence of learning outcomes of Light Vehicle Engine Maintenance (PMKR) between students who get the Problem Based Learning (PBL) learning model and learning motivation on sent learning outcomes with conventional learning models, 2) There is an interaction between the PBL learning model and learning motivation on learning outcomes in PMKR lessons. 3) There are differences in the PMKR learning outcomes of students who have high learning motivation who receive the PBL learning model treatment. 4) There are differences in learning outcomes of light vehicle engine maintenance students who have low learning motivation who get the PBL learning model. This study used an experimental method with a 2 x 2 factorial design. The population was 80 students, the sample to be used was 66 students taken using smple random sampling technique. Then from the 66 students into 2 groups where Group 1 gathered 33 students into the Experiment Class which was taught with the PBL learning model and Group 2 returned 33 students from the Control class who were taught by the conventional model. The results showed that there were differences in learning outcomes between students who received treatment Problem Based Learning learning model and students who received conventional learning model treatment. There is an interaction between the learning model and learning motivation. Students who have learning motivation are more suited to the PBL model, while students who have low learning motivation are more suited to using the conventional model.